Study of the influence of psychological factors on women’s purchasing decisions during e-commerce livestream - L. Jiang; P. Loahavilai; P. Udomwong (Науковий вісник Мукачівського державного університету. Серія "Педагогіка та психологія")
Apart from YouTube and Instagram, new e-commerce live streaming platforms have emerged (TikTok Shopping, Amazon Live), which opens new opportunities for engaging with the audience and driving sales. Women, looking for an emotional and interactive experience, tend to make impulse purchases during live broadcasts. That is why it is necessary to investigate this topic. The purpose of this study was to examine the psychological factors that influence women’s impulse purchases while watching live broadcasts and to determine the psychological characteristics of women who make impulse purchases during live broadcasts. The study included questionnaires and interviews with women living in the Philippines, East Timor, Thailand, Singapore, Myanmar, Malaysia, and Laos. The key findings are that the study revealed the psychological factors of influence and psychological characteristics of women as they make purchases during e-commerce live streams. Psychological characteristics include emotionality while watching (68.3% of respondents), fear of missing out on a good deal (58.3% of respondents) and being influenced by other viewers and streamers (74.2% trust recommendations). Psychological factors include a set of technological and social components. Technological factors include interactivity and real-time communication (56.7% consider it significant); visual appeal and product display (71.7% consider it significant); and the convenience of shopping while browsing. Social factors include parasocial interaction with the streamer, a sense of community with other viewers (63.3%). The study also identified the role of hosts, which plays a significant role in building trust in the product and online platform: building trust in the product and brand (74.2% trust recommendations); influence through charisma, expertise, and attractiveness (62.5% consider them attractive, 58.3% – competent). Live broadcasts effectively stimulate impulse purchases among women. Emotions, trust, and social influence play a key role in this process. The practical significance of this study lies in the possibility of helping women to better understand the factors that influence impulse purchases, to avoid the influence of emotional stimuli and social pressure. The findings of this study can be used to develop recommendations on how people can effectively shop online